Maternal Morbidity and Mortality Associated with Delivery after Intrauterine Fetal Death (Bangladesh Medical Journal, 2009)
To determine the maternal morbidity and mortality associated with delivery after intrauterine fetal death (IUFD) and to find out the place of fetal destructive procedures and cesarean section. The study design was Cross-sectional. The place of study was conducted in the Labour Room, Dhaka Medical College Hospital Dhaka from January 2005 to December 2005.Patients and Methods: All women were included in the present study who presented before the onset of labour pains, after intrauterine fetal death at 26 weeks or onward with singleton pregnancy. Assessment of maternal demographic characteristics, gestational age at fetal demise, delivery -IUFD interval, mode of delivery; vaginal with or without fetal destructive procedures/cesarean section and maternal complications were the main outcome measures. There were 5,502 live birth and 189 deliveries with intrauterine fetal death. Mode of delivery was vaginal in 87.4% and cesarean section in 12.6% of the cases. Thirty six (21%) of the vaginal deliveries were complication by lower urogenital tract injuries in certain cases, whereas 75% (18/24) of patients delivered by cesarean section developed major postoperative complications like postpartum haemorrhage , shock, endometritis, peritonitis and wound dehiscence. No maternal death was identified. Rate of delivery with intrauterine fetal death was 34.3/1000 live -birth deliveries. Maternal morbidity like perineal tear, urinary tract infection, menstrual disorder and even secondary infertility may follow after vaginal mode of delivery by forceps and destructive procedures. The frequency and severity of complications after cesarean delivery are quite higher and may rarely lead to even maternal death. Key Words: Intrauterine fetal death. Maternal morbidity.   DOI: 10.3329/bmj.v38i2.3571 Bangladesh Medical Journal 38(2) 2009 39-43